Towards identification of the scale insects (Hemiptera: Coccomorpha) of continental Africa: 2. Checklists and keys to six archaeococcoid families - Watson, Gillian W. (Zootaxa, 2022)
Scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) feed on plant sap; some are damaging pests in agriculture and forestry. However, the scale insects found in continental Africa have not been extensively studied and the available means of identification are incomplete. This synoptic work, the second in this series, covers the six archaeococcoid scale insect families found in continental Africa: Kuwaniidae, Margarodidae, Matsucoccidae, Monophlebidae, Ortheziidae and Putoidae. The work provides identification keys to a total of 29 genera and 137 species, and a checklist for each family. Pseudaspidoproctus zimmermanni (Newstead) (Monophlebidae) is transferred to Aspidoproctus, as Aspidoproctus zimmermanni (Newstead), comb. n. Praelongorthezia praelonga (Douglas) (Ortheziidae) is recorded from Gambia for the first time.